(untitled) (Global Journal of Human-Social Science, 2023)
A number of well-known historical figures taught themselves to read at 2 or 3 years old but some ordinary children were known to do it too and were called natural readers This research identified children who had taught themselves to read in two different reading teaching eras in England to find out how they had developed their initial sound to symbol awareness The methods these children used were investigated through a freeform writing task that showed their level of handwriting skill and knowledge of the language The results were then shared with Reception year teachers in pilot studies The results showed 30 uplift in reading skill school attainment tests SATs In the main study there were 8 teachers and their 175 pupils Spelling and handw riting coordination scales were developed to profile the skills of the group of students from their data on entry to school at 5 years old after 6 months and again on entry to Year 2age 7 years At each stage all the teachers were sent reports on how to help their individual children